Estudo da variação temporal e espacial da pneumonia em Fortaleza/CE e em Sobral/CE: relação com o clima e variáveis sociais, econômicas e ambientais - Freitas Júnior, Dáviney Sales de (2023)
The present study deals with the associations between climatic elements and hospitalizations for pneumonia, for Fortaleza/CE and Sobral/CE, as well as relating hospitalizations with the socioeconomic and environmental conditions of these cities. This present thesis, which draws a parallel between two urban realities (a metropolis and a medium-sized city), correlates climatic elements with hospitalizations for pneumonia, from the perspective of Geographic Climatology. The climatological data, which were collected at the Pici meteorological station (UFC – Fortaleza) and at the INMET meteorological station in Sobral, were as follows: rainfall, average temperatures, average maximums, average minimums, thermal amplitude, relative air humidity and speed of winds within the 1998-2020 time series. Data on hospitalizations for pneumonia were acquired through the Hospital Information System (SIH) of the online platform (DATASUS), for correlations and multiple linear regressions; and the Ceará State Health Department (SESA). These refer to the neighborhoods of origin of those hospitalized in Fortaleza and Sobral, which were spatialized on the choropleth maps of the two cities, using the ArcMap software. It was found that the highest cases of pneumonia occurred in neighborhoods with characteristics of high social vulnerability, also located in areas of environmental risk, with emphasis on areas along the courses of the Maranguapinho and Cocó rivers (Fortaleza), as well as the Acaraú River (Sobral). Meteorological data were correlated with hospitalizations for pneumonia, considering the group with all age groups. Using the Rstudio software, an output of two correlation matrices was generated: one for Fortaleza and the other for Sobral. All variables were correlated with each other, considering the period of the time series. Rainfalls and average temperatures were the climatic elements that best correlated with hospitalizations for pneumonia in both cities. The Pearson correlations of precipitation data and average temperatures with hospitalizations for Fortaleza were 0.35 and – 0.29, respectively, both with valid statistical significance (p-value). In the case of Sobral, the Pearson correlation values for precipitation x hospitalizations (0.16) and average temperatures x hospitalizations (- 0.36) also had an excellent p-value. The significance numbers presented values of α = 0.01, being a criterion for the selection of such climatological variables, in order to carry out multiple linear regressions, considering a series of assumptions, among them the Shapiro-Wilk test, to construct a regression model for each city. Given the statistical results and socioeconomic and environmental analyzes of the cities of Fortaleza and Sobral, the present study is of utmost importance, both for Geographic Climatology, Epidemiology and other areas of knowledge, also serving as support for policies that meet the needs of Public Health.